Model Matematika Penyebaran Nomophobia - Anjely Aunaya Alfatihah; Muhammad Subhan (Journal of Mathematics UNP, 2022)
Nomophobia is a psychological disease that causes a person to feel dependent on smartphones. In this study, a mathematical model of the spread of nomophobia will be formed. The purpose of the formation of this mathematical model is to provide an overview of the spread of nomophobia. The method used in this study is a descriptive method, namely, analyzing theories regarding the problems discussed. Based on the results of the analysis of the mathematical model of the spread of nomophobia, two fixed points are obtained, namely the disease-free fixed point and the endemic fixed point. Next, the stability of the fixed point will be determined, which shows that the disease-free fixed point is asymptotically stable, while the endemic fixed point is asymptotically stable if βπ>(δ+μ)(γ+μ). The simulation results for the disease-free fixed point show that at a certain time the disease will disappear, while for the endemic fixed point it shows that at a certain time the disease will outbreak if the rate of interaction between susceptible individuals and individuals infected with nomophobia is higher than the rate of individuals who have self-control and individual doing therapy.